2011
DOI: 10.1007/s11434-011-4390-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of coral bleaching using symbiotic zooxanthellae density and satellite remote sensing data in the Nansha Islands, South China Sea

Abstract: Coral bleaching, characterized by a significant loss of symbiotic zooxanthellae, is the primary cause of mass coral mortality and reef degradation throughout the world. The characteristics, processes, and resistance of corals to bleaching varies significantly and is dependent on environmental conditions. We documented a mass coral bleaching event in June 2007 at the Meiji and Zhubi Reefs, Nansha Islands (NS), South China Sea using ecological surveys and measurement of coral zooxanthellae density and sea surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…In the Nansha Islands (i.e., the Spratly Islands, southern South China Sea (SCS)), coral bleaching events, such as GCBEs, are one of the main threats to coral health, and lead to coral reef degradation and macroalgae occupation (e.g., Li et al, 2011;Yu et al, 2006). In situ observation during an investigation in June 2015 found that corals were in a healthy state such that almost no bleaching corals were found (e.g., Qin et al, 2019).…”
Section: 1029/2019jc015579mentioning
confidence: 99%
“…In the Nansha Islands (i.e., the Spratly Islands, southern South China Sea (SCS)), coral bleaching events, such as GCBEs, are one of the main threats to coral health, and lead to coral reef degradation and macroalgae occupation (e.g., Li et al, 2011;Yu et al, 2006). In situ observation during an investigation in June 2015 found that corals were in a healthy state such that almost no bleaching corals were found (e.g., Qin et al, 2019).…”
Section: 1029/2019jc015579mentioning
confidence: 99%
“…6d). In June 2007, bleaching events were observed on Zhubi Reef and Meiji Reef of Nansha Islands (Li et al, 2011) when NOAA DHW and TSA_DHW here were both less than 3℃-weeks. If the DHW threshold of 4℃-weeks based on satellite data really underestimates the extent and intensity of coral bleaching in SCS, corals affected in these two years might be tremendous especially in 1998.…”
Section: Anomaly Intensitymentioning
confidence: 99%
“…Reefs near Philippines such as the northern Palawan Islands (10°24′-11°38′N, 119°10′-120°30′E) and Bolinao (16°22′-16°27′N, 119°52′-119°59′E) experienced vast area bleaching in 1998 (Arceo et al, 2001), indicating coral reefs of China may also have suffered from this extreme thermal event. Then in June 2007, in situ data found the initial stage of coral bleaching on Zhubi Reef and Meiji Reef (Li et al, 2011) of the Nansha Islands due to abnormally high temperatures. In addition, coral records show that coral reefs in the southern SCS have experienced frequent bleaching events due to elevated SST over the last 200 years (Yu, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, bleaching susceptibility also varies according to coral species, location, thermal history, environmental acclimatization capability, and Symbiodiniaceae (i.e., zooxanthellae) genotype (e.g., Berkelmans & van Oppen, ; Liang et al, ; Loya et al, ; Thompson & van Woesik, ). For example, in the Luhuitou fringing reef of the South China Sea (SCS), branching Acropora corals had lower ZD and yet were more susceptible to bleaching than massive Porites corals (Li et al, ; Xu et al, ). The same susceptibility pattern was observed over a wide geographic range.…”
Section: Introductionmentioning
confidence: 99%